1982
DOI: 10.1002/chin.198211273
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PHENOPHOSPHAZINES. V. 7,12‐DIHYDROBENZO(A)PHENOPHOSPHAZINES

Abstract: N‐Phenyl‐ 2‐aminonaphthalin (I) wird durch Thiophosphorsäuretrichlorid (II) zum 12‐Chlor‐12‐ thio‐7,12‐dihydrobenzo[a]phenophosphazin (III) cyclisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The emission of both PTP and PT is weak and exhibits a large Stokes shift (see Figures and ). Triphenylphosphine also exhibits a large Stokes shift, with emission occurring between 450 nm and 500 nm, depending on the polarity of the solvent used (450 nm in diethyl ether and 475 nm in acetonitrile). , In triphenylphosphine, this emission is assigned as a π*→ n transition, as triphenylphosphine oxide emits at 290 nm with a small Stokes shift. A large Stokes shift typically indicates a change in geometry from the ground state to the excited state, and for triphenylphosphine, this is believed to be a fast geometrical conversion from a pyramidal ground state to a more-planar excited state .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission of both PTP and PT is weak and exhibits a large Stokes shift (see Figures and ). Triphenylphosphine also exhibits a large Stokes shift, with emission occurring between 450 nm and 500 nm, depending on the polarity of the solvent used (450 nm in diethyl ether and 475 nm in acetonitrile). , In triphenylphosphine, this emission is assigned as a π*→ n transition, as triphenylphosphine oxide emits at 290 nm with a small Stokes shift. A large Stokes shift typically indicates a change in geometry from the ground state to the excited state, and for triphenylphosphine, this is believed to be a fast geometrical conversion from a pyramidal ground state to a more-planar excited state .…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (CDCl 3 ): δ 7.37-7.27 (m, 10H), 7.17 (dd, J ) 4.2, 2.3 Hz, 1H), 7.01 (ddd, J ) 4.8, 3.7, 1.2 Hz, 1H). 31 P{ 1 H} NMR (CDCl 3 ): δ 19 (s).…”
Section: 5-bis(diphenylphosphino)thiophene (Ptp)mentioning
confidence: 99%
“…McHattie obtained a number of amides of thiophenophosphazinic acid (34) by heating a benzene solution of the acid chloride 22a with ammonia or a primary or secondary amine. These amides are tabulated in Mann's book.8 Several other amides of 34 were later prepared by a similar procedure15 and are mentioned in section VI.…”
Section: Halogenationmentioning
confidence: 99%
“…It was concluded that the phosphorus atom was so remote from the reaction center in these cases that the differences in their electronic effects were not manifest. Thiophenophosphazinic acid (34) was first prepared by Haring,5 who noted that it was soluble in aqueous Na2C03 and that it could be reprecipitated with HC1.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%